Advances in Multiferroic Nanomaterials Assembled with Clusters. (19th March 2015) - Zhao, Shifeng
Abstract : As an entirely new perspective of multifunctional materials, multiferroics have attracted a great deal of attention. With the rapidly developing micro- and nano-electro-mechanical system (MEMS&NEMS), the new kinds of micro- and nanodevices and functionalities aroused extensive research activity in the area of multiferroics. As an ideal building block to assemble the nanostructure, cluster exhibits particular physical properties related to the cluster size at nanoscale, which is efficient in controlling the multiferroic properties for nanomaterials. This review focuses on our recent advances in multiferroic nanomaterials assembled with clusters. In particular, the single phase multiferroic films and compound heterostructured multiferroic films assembled with clusters were introduced detailedly. This technique presents a new and efficient method to produce the nanostructured multiferroic materials for their potential application in NEMS devices.